2019
DOI: 10.1111/ene.14028
|View full text |Cite
|
Sign up to set email alerts
|

Early efficacy and late gain in chronic and high‐frequency episodic migraine with onabotulinumtoxinA

Abstract: Background and purpose The aim was to analyse the clinical characteristics of a long‐term follow‐up of patients with chronic and high‐frequency episodic migraine in treatment with onabotulinumtoxinA. Methods Patients diagnosed with high‐frequency episodic migraine (HFEM) or chronic migraine (CM) according to the International Classification of Headache Disorders 3 beta were included. A comparative analysis was carried out at each study time point identifying outcome measures according to initial diagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
4
17
0
Order By: Relevance
“…Onabotulinumtoxin A (BT-A) is a safe and effective preventive treatment for CM, as shown in the Phase 3 Research Evaluating Migraine Prophylaxis Therapy (PREEMPT) trials [8][9][10][11][12]. Several real-life studies confirmed its safety and efficacy in clinical practice [13][14][15][16][17][18][19][20][21][22] and showed that a shorter disease duration, some characteristics of headache (ocular, imploding), allodynia, and the absence of medication overuse and depressive symptoms are predictors of clinical response [23][24][25][26][27][28][29][30][31][32][33]. However, it is common experience to observe fluctuations in the clinical response to BT-A as to other preventive treatments.…”
Section: Introductionmentioning
confidence: 97%
“…Onabotulinumtoxin A (BT-A) is a safe and effective preventive treatment for CM, as shown in the Phase 3 Research Evaluating Migraine Prophylaxis Therapy (PREEMPT) trials [8][9][10][11][12]. Several real-life studies confirmed its safety and efficacy in clinical practice [13][14][15][16][17][18][19][20][21][22] and showed that a shorter disease duration, some characteristics of headache (ocular, imploding), allodynia, and the absence of medication overuse and depressive symptoms are predictors of clinical response [23][24][25][26][27][28][29][30][31][32][33]. However, it is common experience to observe fluctuations in the clinical response to BT-A as to other preventive treatments.…”
Section: Introductionmentioning
confidence: 97%
“…The time of the evolution of migraine has been elucidated as one of the most important factors for a better treatment outcome . Our results also highlight the importance of starting treatment with OnabotulinumtoxinA earlier in the course of the disease in young patients even when the diagnosis is high‐frequency EM since this population is equally disabled . However, this is not always easy due to the delay in diagnosis or in reaching specialized headache units .…”
Section: Discussionmentioning
confidence: 68%
“…In order to be able to clinically deep phenotype our patients and to better understand migraine and its process of chronification, we decided to identify the clinical predictors of excellent and no‐response, being these opposite ends of the spectrum of response to preventive treatment with OnabotulinumtoxinA. So, we did a secondary analysis of the study done on the evaluation of the efficacy and late gain in CM in high‐frequency episodic migraine (EM) with OnabotulinumtoxinA …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Onabotulinumtoxin A (BT-A) is a safe and effective preventive treatment for CM, as shown in the Phase 3 Research Evaluating Migraine Prophylaxis Therapy (PREEMPT) trials [7][8][9][10][11]. Several real-life studies confirmed its safety and efficacy in clinical practice [12][13][14][15][16][17][18][19][20][21] and showed that a shorter disease duration, some characteristics of headache (ocular, imploding), allodynia, and the absence of medication overuse and depressive symptoms are predictors of clinical response [22][23][24][25][26][27][28][29][30][31][32]. However, it is common experience to observe fluctuations in the clinical response to BT-A as to other preventive treatments.…”
Section: Introductionmentioning
confidence: 97%